BREMSO: a simple score to predict early the natural course of multiple sclerosis. (25th March 2015) - Bergamaschi, R.; Montomoli, C.; Mallucci, G.; Lugaresi, A.; Izquierdo, G.; Grand'Maison, F.; Duquette, P.; Shaygannejad, V.; Alroughani, R.; Grammond, P.; Boz, C.; Iuliano, G.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose Early prediction of long‐term disease evolution is a major challenge in the management of multiple sclerosis (MS). Our aim was to predict the natural course of MS using the Bayesian Risk Estimate for MS at Onset (BREMSO), which gives an individual risk score calculated from demographic and clinical variables collected at disease onset. Methods An observational study was carried out collecting data from MS patients included in MSBase, an international registry. Disease impact was studied using the Multiple Sclerosis Severity Score (MSSS) and time to secondary progression (SP). To evaluate the natural history of the disease, patients were analysed only if they did not receive immune therapies or only up to the time of starting these therapies. Results Data from 14 211 patients were analysed. The median BREMSO score was significantly higher in the subgroups of patients whose disease had a major clinical impact (MSSS≥ third quartile vs. ≤ first quartile, P < 0.00001) and who reached SP (P < 0.00001). The BREMSO showed good specificity (79%) as a tool for predicting the clinical impact of MS. Conclusions BREMSO is a simple tool which can be used in the early stages of MS to predict its evolution, supporting therapeutic decisions in an observational setting.